Breaking the Cycle of Drugs and Crime in Birmingham, Alabama, Jacksonville, Florida, and Tacoma, Washington, 1997-2001 - Harrell, Adele V. ([Verlag nicht ermittelbar], 2004)
This study was an evaluation of the Breaking the Cycle (BTC) demonstration projects conducted in Birmingham, Alabama, Jacksonville, Florida, and Tacoma, Washington, between 1997 and 2001. The BTC demonstrations tested the feasibility and impact of systemwide interventions to reduce drug use among offenders by identifying and intervening with drug-involved felony defendants. This study contains data collected as part of the impact evaluation of BTC, which was designed to test the hypotheses that BTC reduced criminal involvement, substance abuse, and problems related to the health, mental health, employment, and families of felony drug defendants in the demonstration sites. The evaluation examined the relationship between changes in these areas and characteristics of the participants, the kinds and levels of services and supervision they received, and perceptions of defendants about the justice system's handling of their cases. It also assessed how BTC affected case handling and the length of time required to reach a disposition, the number of hearings, and the kinds of sentences imposed. The impact evaluation was based on a quasi-experimental comparison of defendants in BTC with samples of similar defendants arrested in the year before BTC implementation. Interviews were conducted with sample members and additional data were gathered from administrative records sources, such as the BTC programs, arrest records, and court records.